2018
DOI: 10.1097/inf.0000000000001837
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Otitis Media in the Pediatric Emergency Department

Abstract: Adherence rate to the local guidelines treatment recommendations for uncomplicated AOM was high, as measured by whether appropriate treatment was given and type and duration of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Still, this project is the first published report conducted in a pediatric UC setting. 9 , 15 , 17 , 22 , 23 This initiative may not be generalizable to all UC centers because ours took place in an extensive academic UC network with a sophisticated EHR and robust QI support. However, these education interventions could be easily replicated to any group of clinicians without significant expense or difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Still, this project is the first published report conducted in a pediatric UC setting. 9 , 15 , 17 , 22 , 23 This initiative may not be generalizable to all UC centers because ours took place in an extensive academic UC network with a sophisticated EHR and robust QI support. However, these education interventions could be easily replicated to any group of clinicians without significant expense or difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may play a role is doubts regarding follow-up, which lead to more cautious therapeutic and diagnostic plans. In a study that found around 20% of antibiotics were wrongly prescribed, 74% of patients were not examined by a physician prior to the emergency department visit [ 6 ]. This may explain why most of the patients were treated inappropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate treatment of acute otitis media (AOM) is a well-described phenomenon in the outpatient setting [1][2][3][4][5] and leads to unnecessary adverse drug events and increased bacterial resistance. 6,7 To our knowledge, the treatment of AOM in the inpatient setting, apart from its complications, has not been described.…”
mentioning
confidence: 99%